Фінанси соціального захисту сільського населення - Насібова, Ольга Вікторівна (Дніпропетровський державний аграрний університет, 2020)
У статті досліджено фінансове забезпечення соціального захисту сільського населення. Визначено особливості становлення та формування фінансових відносин системи соціального захисту сільського населення. Проведено аналіз структури та динаміки загальних доходів домогосподарств у сільській місцевості у 2009-2018 роках. Виявлено джерела фінансового забезпечення соціального захисту сільського населення. Виокремлено проблемні питання забезпечення соціального розвитку сільських територій та шляхи їх вирішення. Встановлено наявність стабільної тенденції до зростання ролі оплати праці, пенсійних виплат, доходів від продажу сільськогосподарської продукції та підприємницької діяльності і самозайнятості у формуванні доходів сільських домогосподарств. Визначено вплив соціально-демографічних особливостей складу сільських домогосподарств на формування фінансового забезпечення соціального захисту сільського населення та розвиток сільських територій.

In the conditions of transformational transformations of the agrarian sector of the economy and intensification of political instability in Ukraine, raising the standard of living and economic well-being of the rural population remain topical issues. Of particular importance is the need to improve the mechanisms of the social protection system of the rural population and increase the efficiency of its financial support, due to a number of negative factors, which together lead to increased social exclusion of rural citizens and limited realization of their socio-economic potential. The article examines the financial support of social protection of the rural population. Peculiarities of formation and formation of financial relations of the system of social protection of the rural population are determined. An analysis of the structure and dynamics of total household incomes in rural areas in 2009-2018 was conducted. Sources of financial support for social protection of the rural population have been identified. Problematic issues of ensuring the social development of rural areas and ways to solve them are highlighted. There is a stable tendency to increase the role of wages, pensions, income from the sale of agricultural products and entrepreneurial activities and self-employment in the formation of income of rural households. The influence of socio-demographic features of rural households on the formation of financial support for social protection of the rural population and the development of rural areas is determined. At the present stage of socio-economic development of the state remain unresolved problems of unemployment, poverty, large-scale labor migration of rural population and underdeveloped social infrastructure of villages, which is necessary to reproduce labor, increase productivity, promote comprehensive and harmonious personal development. Degradation of rural areas undermines the foundations for further development of the agricultural sector, poses a threat to food security in the country. The effectiveness of financial provision of social protection of the rural population increases the level and quality of life of citizens in rural areas, promotes dynamic and harmonious development of people, social justice and poverty reduction, which ensures stability and successful economic development of rural areas.
Finances of social protection of the rural population
Keywords: фінанси; фінансове забезпечення; соціальний захист; соціальний розвиток; сільське населення; сільська громада; finance; financial security; social protection; social development; rural population; rural community